HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TERHADAP KEJADIAN STUNTING DI DESA SECANGGANG KABUPATEN LANGKAT - TAUFIQ ASRI MUNANDAR; ROBITAH ASFUR (JURNAL ILMIAH SIMANTEK, 2021)
Stunting is one of the most significant inhibiting factors for development and globally affects around 162 million childrenunder 5 years of age, defined as less than -2 standard deviations (SD) based on child growth standards according to theWorld Health Organization (WHO). National Stunting prevalence in 2013 was (37.2%), which means an increase comparedto 2010 (35.6%) and 2007 (36.8%). One important factor influencing nutritional status in infants is the mother's knowledgeabout nutrition in infants. Lack of mother's knowledge about the diversity of materials and diversity of food types will disruptthe process of growth and development of infants, especially brain development, therefore mothers need to provide nutritiousfood intake to their children. This study aims to relate the level of community knowledge to the incidence of stunting inSecanggang Village, Langkat Regency. This research uses a descriptive-analytic method with a cross-sectional design. Datawere processed using the SPSS Chi-Square test. The results showed that the relationship between the level of communityknowledge and the incidence of stunting in Secanggang Village, Langkat Regency showed a p-value of 0.004 (p <0.05).There is a significant correlation between the level of community knowledge on the incidence of stunting in SecanggangVillage, Langkat Regency.